What's trending in libraries from the internet cybersphere – digital clutter. Issue 2 (4th April 2016) - Oyelude, Adetoun A.
Abstract : Purpose: This is the first edition of the column for 2016. Design/methodology/approach: The vignettes from the Internet this year will be mainly from blogs. Findings: This edition covers issues germane mainly to libraries, technology use and maintenance of digital devices used. Research limitations/implications: Executives in the IT industry may be looking at three major issues in 2016. Practical implications: More often than not, internal vulnerabilities exceed external security threats. Social implications: Businesses must define and set the standards of what good and bad security practices look like. Originality/value: IT teams should restrict the extent that outside devices can connect and roam around on proprietary corporate networks and also work to ensure that employees are educated on the company's security policy.